تطبيق نموذج فيركلاف على خطاب مارتن لوثر كينغ جونيور لدي حلم - بن عروس Abdusalam Mohamed (مجلة الاصالة, 2024)
The King’s speech is an important part of American civil rights history. King uses speech techniques, language patterns, and persuasive language tools and techniques in order to involve the audience and advance fairness and righteousness. With this analysis, readers can track King’s decisions in language such as pronouns, word choices, and rhetorical appeals used such as ethos, pathos and logos and analyze the effects on society. This paper investigates how his speech generates a sense of unity, hope, collective